1875–1876 Ala. Acts 82, Rev. Code, ch. 9, § 7(15) - (:unkn) unknown (General Publisher, 1875)
Imposed tax rate of 0.75% of the value of any pistols, guns, dirks, and Bowie knives.
--
Keywords: TAX - PROPERTY OR SALES